Necrozoospermia: The tree that hides the forest. (16th March 2022) - Boursier, Angèle; Dumont, Agathe; Boitrelle, Florence; Prasivoravong, Julie; Lefebvre‐Khalil, Valérie; Robin, Geoffroy; Barbotin, Anne‐Laure
Abstract: Background: Necrozoospermia is a condition found in 0.2%–0.4% of male infertility cases. The causes of necrozoospermia are multiple: they can be related to testicular and/or post‐testicular damage. Additionally, these causes most often involve the production of reactive oxygen species (ROS) and/or sperm DNA fragmentation (SDF) which can reduce the chances of spontaneous pregnancy or affect the outcome of assisted reproductive technologies. Objective: To focus on potential etiologies of necrozoospermia, its diagnosis and its therapeutic management especially before the employment of ICSI. Methods: Authors searched PubMed/Medline, Web of Science, Cochrane Library, Google and Institutional websites for medical subheading terms and free text words referred to "necrozoospermia", "sperm vitality", "sperm viability", SDF and "ICSI". Results: We identified 12 main etiologies of necrozoospermia responsible for either a decrease of sperm vitality, a mild, a moderate or a severe necrozoospermia. In case of a confirmed decreased vitality, a thorough check‐up should be conducted and if available, etiological treatment should be proposed. Therapeutic management could also include repeated ejaculations, drug treatments, the use of ICSI with ejaculated or surgically extracted spermatozoa in case of a non‐treatable necrozoospermia. Discussion and conclusion: The potential causes of necrozoospermia should be investigated because many of them could be corrected, thus avoiding the use of ICSI. Moreover, if ICSI procedure remains necessary, the therapeutic management of necrozoospermia could also improve the chances of success by reducing oxidative stress and/or SDF.